2017
DOI: 10.1016/j.msea.2017.05.104
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue crack growth behavior in gradient microstructure of hardened surface layer for an axle steel

Abstract: A B S T R A C TThis paper experimentally investigated the behavior of fatigue crack growth of an axle steel with a surface strengthened gradient microstructure layer. First, the microstructure, residual stress and mechanical properties were examined as a function of depth from surface. Then the fatigue crack growth rate was measured via three point bending fatigue testing. The results indicated that fatigue crack growth rate decelerated first and then accelerated with the increase of crack length within the gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Due to the combined effects of gradually decreasing residual compressive stress and the gradually increasing crack length, J Δ path starts to increase gradually when the crack propagates from 3.9 mm. This variation in J Δ path can be adopted to explain crack arrest at the crack length of 3 mm in high-cycle fatigue experiments on train axle steel [52]. Fig.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the combined effects of gradually decreasing residual compressive stress and the gradually increasing crack length, J Δ path starts to increase gradually when the crack propagates from 3.9 mm. This variation in J Δ path can be adopted to explain crack arrest at the crack length of 3 mm in high-cycle fatigue experiments on train axle steel [52]. Fig.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…Many literatures [48][49][50][51] have shown that the residual compressive stress resulted from surface mechanical treatment could effectively improve the fatigue resistance. More recently, Zhang et al [52] studied experimentally the fatigue crack-growth behavior in gradient axle steel with residual stress. The authors reported crack arrest in the gradient layer under relatively low stress amplitude, which was a resultant of compressive residual stress.…”
Section: Introductionmentioning
confidence: 99%
“…However, although existing studies have revealed the positive effect of gradient structure on fatigue performance, there is still insufficient understanding of how gradient rate precisely regulates the fatigue life, crack initiation threshold, and cyclic deformation behavior, which undoubtedly constitutes a technological bottleneck restricting the further optimization and industrialization of its application [35,36]. Furthermore, with no sophisticated methods for controlling gradient rates [34], researchers urgently need to conduct more systematic and in-depth research to reveal the intrinsic law between the gradient rate and the key properties of gradient structural steel, establish accurate performance prediction models, and explore efficient and economical preparation processes to achieve precise control of gradient structure [37].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [15] analyzed the fatigue strength of the CRH2 motor bogie frame through simulation and online tests. Zhang et al [16] studied the fatigue crack growth behavior in the gradient microstructure of the surface layer of S38C axle steel. The results indicated that the crack growth rate firstly decelerated and then accelerated with increasing the crack length in the gradient layer.…”
Section: Introductionmentioning
confidence: 99%